GENETIC CHARACTERIZATION OF AVIAN INFECTIOUS BRONCHITIS VIRUS ISOLATES RECOVERED IN CIS COUNTRIES IN 2015–2017 - L. O. Scherbakova; S. N. Kolosov; Z. B. Nikonova; N. G. Zinyakov; Ye. V. Ovchinnikova; I. A. Chvala (Ветеринария сегодня)
Avian infectious bronchitis virus is a cause of major economic losses in poultry industry. However, control of the virus is very complicated due to its high variability. The mutation frequency in the hypervariable region of the S1 gene of the virus isolated from the vaccinated birds annually amounts to 1.5%. Long-term observations of the circulation of IBV isolates detected in a number of poultry farms demonstrated that the virus genetic lineages circulating on the poultry farms could eventually change. This stipulates the need for the continuous monitoring of the virus isolates for the prevention schedule optimization. The paper demonstrates test results of 840 biological samples collected from chickens on the poultry farms in Russia and some CIS countries in 2015–2017. From 311 positive samples 147 IBV isolates were recovered, the majority of which belonged to eight genetic lines of GI genotype: GI-1, GI-12, GI-13, GI-14, GI-16, GI-19, GI-22, GI-23. Moreover, recombinant isolates were detected as well as variant isolates that belonged to none of the known genotypes.